The United States Economy : Performance and Issues - Horiguchi, Yusuke (International Monetary Fund, 1992)
This book, by a staff team headed by Yusuke Horiguchi, examines U.S. economic policy and performance in the 1980s, during which the United States enjoyed its longest peacetime expansion. Notwithstanding the buoyant growth and declines in inflation, the economy experienced low savings, current account deficits, swings in the dollar exchange rate, and structural problems--relating to the strength of financial institutions, the tax system, health care, and productivity.